What is the role of the shareholders vis-a-vis other security holders within the context of shareholder corporate governance with, respect to South African companies act 2008? - Maleya, Mary Reba Chabeda (Centre for Law and Society, 2026)
Post-Apartheid South Africa is an altogether different place politically, socially and economically. Due to the rapid changes since 1994, several laws have been amended or repealed to reflect the newly found democracy. One such law is the Companies Act. This paper examines the proposed Companies Act 71 of2008 together with its 1973 counterpart with special emphasis on the definition and role of the shareholder for corporate governance purposes. In this paper, I seek answers to the following questions: Has the definition of the term shareholder for purposes of corporate governance changed in the proposed Act? Can one confer upon other security holders rights previously exclusively reserved for the traditional shareholder? What the real implications are if any, of such conferment? Whether effectively the position of the traditional shareholder has been usurped or weakened or remains the same? Whether there is a shift in the corporate governance ideology within the new proposed legislation in the South African context and who the real beneficiaries are? In seeking answers to the above questions, this paper consequently examines the various definitions of a shareholder including those under the current and . proposed Companies Acts and further carries out a comparative analysis between South Africa and a three other jurisdictions. It also examines the definitions and rights accruing to the other security holders not traditionally deemed as shareholders. It then examines whether there has been conferment of governance rights previously exclusive to traditional shareholders upon these other security holders and the effects of such conferment if any. Lastly, the paper examines whether there is a paradigm shift in corporate governance ideology within the jurisdiction and whether or no_t it is ideal for the South African context.